Assessment of upper to lower body segment ratio and arm span to height difference in school children of Lahore - Baig, Usman; Mehdi , Syed Muslim; Iftikhar, Nosheen (Journal of the Pakistan Medical Association, 2023)
Objective: To assess upper-to-lower body segment ratio and arm span to height difference in children. Method: The descriptive, cross-sectional study was conducted in schools of the Raiwind area near Lahore, Pakistan, from November 2021 to May 2022, after approval from the ethics review committee of the Sharif Medical and Dental College, Lahore. The sample comprised children aged 3-14 years whose height fell between the 3rd and 97th centiles on the Centers for Disease Control and Prevention height-for-age chart. Data was analysed using SPSS 23. Results: Of the 1,836 children, 906(49.3%) were boys with mean age 8.45±3.02 years, mean height 132.54±17.78cm and mean weight 32.0±13.72kg. Besides, there were 930(50.7%) girls with mean age 8.26±3.21 years, mean height 130.41±18.03cm and mean weight 31.09±13.88kg. The mean upper-to-lower body segment ratio in boys was 1.06±0.15 at age 3 years, 0.96±0.08 at age 7 and 0.94±0.08 at age 10. The mean upper-to-lower body segment ratio in girls was 1.08±0.08 at age 3 years, 0.98±0.07 at age 7, and 0.92±0.10 at age 10. The mean arm span to height difference in boys was -1.81±5.83 and in girls -4.09±5.77. Conclusion: Upper-to-lower body segment ratio and arm span to height difference may help paediatricians in the evaluation of disproportionate short stature. Key Words: Upper to lower body segment ratio, Body proportions, Children, Arm span to height difference, Pakistan.